Chart of North and South America, including the Atlantic and Pacific Oceans, with the nearest Coasts of Europe, Africa, and Asia [sheet 2] - Jefferys, Thomas, d. 1771; Green, John fl. 1730-1753 (Robert Sayer and John Bennett (Firm), 1775)
18th century Copper engraving handcolored with watercolor. Mounted on linen. Outline color. Relief shown pictorially. Middle portion of 3-sheet map. This map was issued as 6 sheets (in this case 3 sheets, but each of those is a joined pair). The first sheet is titled as the map, however each sheet also has its own headings. The UW holds only the first two sheets out of three. Title taken from sheet 1. Printed along left side of top border: ”Chart containing the Coasts of California, new Albion, and Russian Discoveries to the North, with the Peninsula of Kamtschatka, in Asia, opposite thereto; And Islands dispersed over the Pacific Ocean, to the North of the Line.” Printed along the right side of the top border: ”North America and The West Indies with the opposite Coasts of Europe and Africa.” Printed beneath both the left and right side of the bottom border: ”Publish’d according to Act of Parliament, 10 June 1775, by Robt. Sayer & J. Bennett, No. 53 in Fleet Street.” Printed within the Atlantic Ocean next to Africa are two charts listing astronomical observations made from the east coast of North America and the north coast of South America. Printed beneath in the northwest of North America is a table of coordinates for islands in the Pacific Ocean according to several explorers including Francisco de Gualles, Sebastian the Biscayner, Jo. Rodr. Cabrillo and Francisco de Ulloa. Printed above this table: ”The American Coast from C. Corientes to Latd. 39.30 N with the Islands to the Westward are laid down chiefly from the Spanish chart, used on board the Cabadonga, taken by Lord Anson in 1743 which is scarce reconcilable with other charts and Journals either as to the Names or Situation of Places.” Printed in the north Atlantic Ocean between North America and the British Isles is a chart explaining the difference in longitude between this chart and the maps of Bellin, D’Anville, and Pople. Printed in the far northwest coast of North America at latitude 47 degrees north: ”In Latd. 47.30 J. de Fuca pretends he enter’d in 1592, in quest of the Straits of Anian, and found a Passage, about 30 Leagues wide through which after 26 days North and North East, he got into the North-Sea.” Printed beneath “New Albion”: ”So Named by Sr. Francis Drake to whom the country was surrendered by the King in 1578.” Printed beneath “Killistins” north of “Sioux” region: ”the Climate of this Land is a great deal more temperate than that of Hudson’s Bay.” Printed on northwest coast of North America at latitude 53 north: ”in Latd. 53 ‘tis pretended that in 1740, Adml. De Fonte enter’d and Sail’d by Lakes and Rivers till he found a Ship (as is supposed in Hudon’s Bay) from Boston in New England.” Shows land in Northwest coast of North America named “Fou Sang” with the following legend: “Land which is Supposed to be The Fou Sang of the Chinese Geographers.” Printed beneath Fou Sang is a legend regarding Spanish explorations by Juan Perez in 1774: ”Coast seen by the Spaniards in 1774 with inhabitants which go naked.” Shows routes of several explorers, their ships, and dates of exploration including Captain Behring in 1741, George Anson in 1742, Van Noorte 1599, N.S. de Cabadonga and the Centurion in 1743, Alvaro de Mendaña in 1568, and John Byron in 1765. Depicts Kamschatka in Russia as well as the “Aleutskiai Isles” and the “Sea of Olutorskiai Isles”. Depicts many regions in North America including “New Albion” as north of California, New Mexico, Louisiana, West and East Florida, Georgia, South Carolina, North Carolina, Virginia, Pennsylvania, Maryland, New Jersey, New York and “New England.” Also visible in North America is a river running from the northwest to the Pacific Ocean named “River of the West.” Within North America several areas in which Native American tribes are labeled including Apaches, Chikasaws, the Cherokees, and the Sioux. Shows the “Caribbean Sea” and the islands of the West Indies as well as the Gallapagos Islands, the Azores and Cape Verd Islands in the Atlantic, Spain, France, the “British Isles,” and the western coast of North Africa. In Africa, several regions are visible including Barbary, “Marocco,” “Zwenziga,” “Zanhaga,” “Senegambia,” and “Guinea.” The “Sahra or Desert of Barbary” is labeled as the Sahara Desert. Depicts small ships along the dashed lines of different explorers’ routes. Prime Meridian: London and Isle of Ferro. Scale c.a. 1:5,5000,000. Thomas Jefferys (c.a. 1710-1771) was one of the most significant English cartographers of the eighteenth century. Working as an engraver, geographer and publisher, he created some of the most important English and American maps of his day. He was appointed Geographer to Frederick Prince of Wales in 1748 and later served as Geographer to George III. One of his first maps is a "Plan of London and Westminster" (1732). His other works include Kitchin's "Small English Atlas" (1749), ""Map of Staffordshire" with Parson and Bowles (1747), engravings for Salmon's "Geography" (1749), a last published edition of Saton's "Atlas" (1752), and "Maritime Ports of France" (1761). Between 1751 and 1768, he published a number of other maps, mainly of America and the West Indies including Fry and Jefferson's "Virginia" (1751), "Nova Scotia" (1755), De Braham's "Carolina"' (1757), "St. Lawrence" by Captain cook (1760), a volume on "Spanish Islands and West Indies' (1762), and "Topography of North America and the West Indies" (1768). He also surveyed and engraved "county maps of Bedfordshire" (1765), "Hampshire" (1766), "Oxfordshire" (1766-7), "Durham and West" (1768), "Buckinghamshire" (1770) and "Yorkshire" (1767-70). Despite his prolific nature, Jefferys found himself bankrupt in 1765. Many of his plates were acquired by Robert Sayer who published much of Jeffreys' work in "North American Atlas" (1775), "West Indian Atlas" (1775) and "North American Pilot" (1775). Jefferys later partnered with William Faden who received Jeffreys' shop when he died in 1771 (Tooley 335). John Green (fl. 1730-53, d. 1757) constructed many maps and globes. His name was a pseudonym for Braddock Mead. His works include "North and South America" (6 sheets) for Jefferys (1753) and a second edition of the map in 1768 (Tooley, 262). Robert Sayer (1725-1794) was a publisher and map and print seller who published much of his contemporaries' work including the work of Thomas Kitchin, Belin and d'Anville (Moreland and Bannister, 172). He worked with Philip Overton beginning in 1745 utnil Overton died in 1751. Sayer then continued to work on his own. He published Rocque's small "British Atlas" (1753), "map of Atlantic" (1757) and "Large English Atlas" (1760). He later collaborated with Herbert and reissued many works by John Senex (?-1740). After cartographer, Thomas Jefferys, went bankrupt, Sayer took some of Jeffreys' assets and with Jefferys published "General topographic map of North America and the West Indies" (1768) and "Middle British Colonies in America" (1768, 1775). In 1770, Sayer was joined by John Bennett. In 1771, Jefferys died and most of his business passed to William Faden while some of his plates stayed in Sayer's hands. Sayer and Bennet then published "General Atlas" (1773), "North American Atlas' (1775), "North American Pilot" (1775-6), "American Military pocket Atlas" (1776), "West India Atlas" (1775), and "Complete Channel Pilot" (1781). In 1781 Bennett retired and then died in 1787. Sayer continued to work on his own until his own retirement in 1792. He then sold his plates and business to Robert Laurie and James Whittle (Tooley, 561). This map was first published June 10, 1775 though it was created earlier by Jefferys with the aid of John Green (fl. 1730-1753). Each section of the map seems to be a different size. The map shows the legends based on Fonte and Fuca. Wagner notes that this map refers to the Pérez's expedition in 1774 in two legends, the first describing "white and fair Indians" and the second stating "inhabitants which go naked" (Wagner, 343, entry 649). Source(s): Moreland, Carl and David Bannister. "Antique Maps: A Collector's Handbook." New York: Longman Group, Ltd., 1983. Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979. Wagner, Henry R. "The Cartography of the Northwest Coast of America to the year 1800 Volume 2." Berkeley: University of California Press, 1937.